Receptor for Advanced Glycation End Products (RAGE) is Expressed Predominantly in Medium Spiny Neurons of tgHD Rat Striatum. (1st June 2018) - Shi, Dian; Chang, Joshua W.; Choi, Jaimin; Connor, Bronwen; O'Carroll, Simon J.; Nicholson, Louise F.B.; Kim, Joo Hyun
Highlights: RAGE expression extended laterally in the CPu of tgHD rats. RAGE was predominantly expressed in the medium spiny neurons (MSN) of the CPu of tgHD rats. RAGE colocalized most extensively with N-carboxymethyllysine (CML) in the MSNs of tgHD rats. RAGE expression and RAGE-ligand colocalization were unaffected by the age of tgHD rats and rostro-caudal axis of their CPu. Abstract: Receptor for advanced glycation end products (RAGE) is a multi-ligand receptor involved in the pathology of several progressive neurodegenerative disorders including Huntington's disease (HD). We previously showed that the expression of RAGE and its colocalization with ligands were increased in the striatum of HD patients, increasing with grade severity, and that the pattern of RAGE expression coincided with the medio-lateral pattern of neurodegeneration. However, the exact role of RAGE in HD remains elusive. In order to address the necessity for a direct functional study, we aimed to characterize the pattern of RAGE expression in the transgenic rat model of HD (tgHD rats). Our results showed that RAGE expression was expanded laterally in tgHD rat caudate-putamen (CPu) compared to wildtype littermates, but the expression was unchanged by disease severity. The rostro-caudal location did not affect RAGE expression. RAGE was predominantly expressed in the medium spiny neurons (MSN) where it colocalized most extensively with N-carboxymethyllysine (CML), which largely contradicts with observations from human HD brains. Overall, the tgHD rat model only partially recapitulated the pattern in striatal RAGE expression in human brains, raising a question about its reliability as an animal model for future functional studies.